Effect of the Convergence of Iranian Consolidation Standard with the International Standard on the Usefulness of Consolidated Information - Farshad Sabzalipour (Shahid Bahonar University of Kerman, 2013)
Abstract Accounting standards are prepared for enhancing the quality of accounting information and performing appropriate informative role. The use of standards and valid rules in preparation and presentation of accounting reports lead to enhance quality of financial reports and usefulness of accounting information for users. This research aims to examine the effect of convergence of the Iranian consolidation standard with the international standard on the usefulness of consolidated information. The research population takes all the companies listed in Tehran Stock Exchange that prepared and presented consolidated financial statements in the years 1381-1389. The multivariable regression model is use to formulate the required valuation and return models, and the generalized least squares method was adopted to test the research hypotheses. Since the consolidation standard has been reviewed in 1384, the models in the periods before and after the year 1384 were individually fitted and the results were compared with each other. The results indicated that the convergence of consolidation standard with the international standard has significant effect on the usefulness of consolidated information.